NILAI-NILAI RELIGI PADA TRADISI HADRAT DI DESA GANDASULI KECAMATAN BACAN SELATAN PROVINSI MALUKU UTARA - Taufik Saman; Ferdinand Kerebungu; Veronika E. T. Salem (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2022)
The hadrat tradition is a religious tradition of the Butonese community in Gandasuli village. With the intention to commemorate Eid al-Adha and prevent people from things that are not wanted. Literally, hadrat can be interpreted as a sacrifice by the Gandasuli community. This study aims to reveal how the Gandasuli village community interprets the hadrat tradition. And also to find out the origin of the birth of this hadrat tradition. The method approach used in this study is a qualitative method which aims to provide a systematic, factual, and accurate description. By describing the data obtained, it is analyzed qualitatively. From the results of this study, it has been found that the Gandasuli village community interprets this tradition as a form of their identity and also how they express their love for the Buton people tradition. However, there are also shortcomings in understanding the meaning of this tradition, especially for the younger generation, this is due to the lack of knowledge of the gandasuli culture. Meanwhile, there are three meanings contained in the hadrat tradition based on the analysis and research results, namely; meaning of unity, religious meaning and aesthetic meaning